Immobilising of anti-HPV18 and E. coli O157:H7 antibodies on magnetic silica-coated Fe3O4 for early diagnosis of cervical cancer and diarrhoea. (24th January 2011) - Hai, Tran Hoang; Phuc, Le Hong; Vinh, Le Khanh; Long, Bui Duc; Kieu, Truong; Bich, Nguyen; Lan, Tran; Hien, Nguyen; Khoa, Le; Tam, Nguyen
This paper presents the synthesis and properties of magnetic silica-coated Fe3 O4 nanoparticles. Uncoated Fe3 O4 nanoparticles with an average diameter of 9-16 nm and saturation magnetisation of around 66 emu/g were first prepared by co-precipitation method. After being coated by SiO2 using the sol-gel method, the diameters of the coated particles ranged from 29 nm to 230 nm and their corresponding saturation magnetisation was reduced to 29 emu/g. The magnetic coated nanoparticles were attached to the monoclonal antibodies of HPV18 and E. coli O157:H7. The TG/DTA analyses indicated that antibodies were attached to the magnetic nanoparticles. The obtained results revealed that magnetic SiO2 -coated Fe3 O4 nanoparticles can be a promising candidate for the diagnosis of cervical cancer at an early stage with high accuracy.